Protein and carbohydrate fractions of common vetch-oat mixtures depending on stage of growth and seeding rate in the mixtures - Marković, Jordan; Vasić, Tanja; Terzić, Dragan; Štrbanović, Ratibor; Knežević, Jasmina; Blagojević, Milomir; Lazarević, Đorđe (Emirates Journal of Food and Agriculture, 2020)
The production and utilization of intercropped legume- cereal bi-crops as ruminant feeds is beneficial for many reasons – legumes are rich in terms of protein concentration, whereas cereals are characterized by higher carbohydrate contents. To improve utilization of common vetch-oat mixtures as feed in Serbia, the objective of this investigation was to evaluate the crude protein (CP) and carbohydrate (CHO) fractions in these feeds using the Cornell Net Carbohydrate and Protein System (CNCPS) depending on the stage of plant development and seeding rate of common vetch and oat in the mixtures. The experiment was conducted at the experimental field of Institute for forage crops, Kruševac – Serbia, in 2015. The field trial was arranged in a randomized block design with three replications. In this research, pure stands of common vetch and oat, and their seed mixtures (common vetch:oat – 1:1.5; 1:1 and 1:0.5) were studied harvested at three different cutting stages: beginning of vetch flowering – 10% of flowering; forming the first pods on 2/3 vetch plants and forming green seeds in 2/3 pods. The samples were analyzed for protein and carbohydrate fractions according to CNCPS. Stage of growth affected significantly all carbohydrate and protein fractions, except unavailable PC fraction of crude protein which did not change with plant growth and development. The highest protein fraction was intermediately degraded PB2 fraction of crude protein. The highest carbohydrate fraction was available cell wall – CB3 fraction of carbohydrate. According to the results obtained in these investigations, it was concluded that common vetch-oat mixtures varied significantly with respect to their carbohydrate and protein fraction. Due to lower CC fraction, oat was superior feed in terms of total carbohydrates supply to ruminants. Among all investigated mixtures and pure stand of oat and common vetch, it could be conclude that mixture with 1:1 common vetch-oat rate was superior because of higher CA and CB3 fractions of total carbohydrate and the highest PB2 fraction of crude protein.